Perspectives from Students: How to Tame the Chaos and Harness the Power of Technology for Learning - Jenny Ge; Rachael E. Smyth; Michelle Searle; Lori Kirkpatrick; Rebecca Evans; Alexa Elder; Heather Brown (Brock University, 2021)
Technology continues to form an important part of the educational landscape, although the value of portable devices as learning tools is still being explored and debated. In light of the technology-based teaching methods suddenly brought into effect in response to the COVID-19 pandemic, the deliberate use of technology for learning is increasingly significant. The purpose of this article is to highlight student perspectives of learning with portable devices to inform the use of portable technology in the Canadian school system going forward. To gather student perceptions, the research team surveyed 704 students in grades 6 to 9 about their use of iPads in the classroom during a 1:1 technology initiative. While students were enthusiastic about the presence of portable technology, they also shared mixed feelings about the use of such technology as a learning tool. Key themes fell into three categories-engagement, inclusivity, and learning-as students shared their insight into the academic, social, and physical barriers that exist as a result of the technology. In the discussion, we identify lessons learned, especially in the area of self-regulation, and make recommendations on how to harness the power of this multi-faceted learning tool and minimize the chaos it can create when not utilized deliberately and carefully.